Stormwater drives seasonal geochemical processes beneath an infiltration basin. Issue 6 (18th October 2022) - McQuiggan, Rachel; Andres, A. Scott; Roros, Andreanna; Sturchio, Neil C.
Abstract: Deicing salt is an important component of road safety during winter storms. Stormwater infiltration best management practices aim to prevent the salt from polluting streams and waterways, but this may shift pollutants to groundwater resources. In response to limited field studies investigating groundwater quality impacts caused by input of salt from stormwater infiltration best management practices, we monitored water levels and quality of groundwater at various depths in an unconfined aquifer around a stormwater infiltration basin using in situ sensors coupled with grab sampling. Our observations revealed differences in groundwater chemistry with depth in the aquifer and processes that were driven by the seasonal changes in the chemistry of stormwater (salt‐impacted in winter and fresh in non‐winter) recharging the aquifer. Water–matrix interactions in the vadose zone beneath the basin affected the transport of sodium (Na) into groundwater following non‐winter recharge. Sodium movement through the aquifer was delayed relative to chloride (Cl), indicating a longer residence time of Na in the vadose zone. Radium (Ra) concentrations were correlated with Cl concentrations, suggesting salt‐impacted recharge caused desorption of Ra into groundwater because of increased salinity. Stormwater‐influenced groundwater followed a preferential flow path due to heterogeneity of the aquifer materials, and water chemistry varied with time and location along the flow path. These results highlight the importance of well screen length, placement and depth, and frequency of observations when designing a monitoring network. Core Ideas: Stormwater infiltration affects groundwater recharge chemistry and water–aquifer matrix interactions. Cl and Na were retained in the vadose zone beneath the basin with lag time between their respective releases. Cl caused desorption of Ra and mobilization into groundwater. Evaporation occurred between stormwater inflow and infiltration to the water table. Stormwater recharge‐influenced groundwater preferentially moved through higher‐permeability layers.